(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Early diagnosis of diabetic nephropathy (DN), the leading cause of death in diabetic patients, is an important issue in preventing and reducing the disease burden for patients and the healthcare system. In this study, we aimed at investigating the value of color doppler ultrasonography in the diagnosis of early diabetic nephropathy (DN). Methods. Two hundred and thirty-eight diabetic patients, were enrolled in this study and were categorized into, either control (n = 109) or study group (n = 129), according to 24 hours urinary albumin excretion rate (UAER), from January 2015 to March 2021. The morphologic findings of the kidneys were observed and compared, in both groups, by color doppler ultrasound technique, and blood flow of renal arteries was also measured, at all levels. Fasting plasma glucose (FPG), uric acid, homocysteine, beta-2- microglobulin, cystatin C, hemoglobin A1c (HbA1c) and CRP were also extracted from their laboratory results. Results. Compared to the control group, the study group had lower intrarenal arterial end-diastolic blood flow velocity (EDV) and higher arterial resistance index (RI) (P < .05). A significant diagnostic value of intrarenal arterial EDV and RI was found for early detection of DN (P < .05). Intrarenal arterial RI and EDV showed positive correlations with UAER, FPG, uric acid, homocysteine, beta-2-microglobulin, cystatin C, HbA1c, and CRP (P < .05). Conclusion. Color doppler ultrasound markers of renal and intrarenal arteries has a high diagnostic value for DN at its early stage. DOI: 10.52547/ijkd.7246